2015
DOI: 10.1002/jps.24377
|View full text |Cite
|
Sign up to set email alerts
|

Zidovudine-Poly(l-Lactic Acid) Solid Dispersions with Improved Intestinal Permeability Prepared by Supercritical Antisolvent Process

Abstract: A supercritical antisolvent (SAS) process for obtaining zidovudine-poly(L-lactic acid) (PLLA) solid dispersions (SDs) was used to attain a better intestinal permeation of this drug. A 3(2) factorial design was used, having as independent variables the ratio 3'-azido-2'3'-dideoxythymidine (AZT)-PLLA and temperature/pressure conditions, as dependent variables the process yield and particle macroscopic morphology. AZT-PLLA production batches were carried out by the SAS process, and the resulting products evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Glibenclamide ASDs prepared by the SAS were shown to have similar solubility as those prepared by solvent evaporation using a rotary evaporator 208 . A recent study further demonstrated improved permeability of zidovudine-poly (l-lactic acid) solid dispersions relative to the pure crystalline drug when tested in an ex vivo everted rat intestinal sac model 224 . The observed effect was attributed to the enhanced poly ( l -lactic acid) (polymer) plasticization which increased the extent of drug diffusion in the polymer matrix.…”
Section: Manufacturing Methods For Preparing Amorphous Solid Dispersionsmentioning
confidence: 95%
“…Glibenclamide ASDs prepared by the SAS were shown to have similar solubility as those prepared by solvent evaporation using a rotary evaporator 208 . A recent study further demonstrated improved permeability of zidovudine-poly (l-lactic acid) solid dispersions relative to the pure crystalline drug when tested in an ex vivo everted rat intestinal sac model 224 . The observed effect was attributed to the enhanced poly ( l -lactic acid) (polymer) plasticization which increased the extent of drug diffusion in the polymer matrix.…”
Section: Manufacturing Methods For Preparing Amorphous Solid Dispersionsmentioning
confidence: 95%
“…Although the EE was higher for the drug:polymer ratio of 1:2, ex vivo experiments that evaluated the intestinal permeability proved higher zidovudine permeation for the 1:1 ratio. This result indicates that the use of SAS method allows the modification of suitable polymeric carrier systems in terms of absorption and dissolution properties of the drug [102].…”
Section: Drug-loaded Particles Using Sasmentioning
confidence: 84%
“…In another study, anti-retroviral drugs presenting low permeability, high dissolution rate and low bioavailability such as zidovudine (3 -azido-2 3 -dideoxythymidine) were considered for their encapsulation into PLLA using SAS, to obtain solid dispersions that improve intestinal absorption [102]. Briefly described, three different zidovudine:PLLA ratios (2:1, 1:1 and 1:2) were formulated in ethanol using three different pressures (P = 135, 100 and 85 bar) while keeping the temperature constant at 45 • C for all runs.…”
Section: Drug-loaded Particles Using Sasmentioning
confidence: 99%
“…In reverse, the drug release is prolonged using a polymer with a hydrophobic behavior, as occurs, for example, by selecting zein [17,[46][47][48][49]. Similarly, a sustained or prolonged release of the active compound was observed from particles based on polylactic acid (PLA) and poly (L-lactic acid) (PLLA) [32,67,98,99,111,112,[118][119][120][121], which, until now, has been mostly employed to deliver anticancer drugs.…”
Section: Sas Coprecipitation Of Active Compounds With Polymeric Carriersmentioning
confidence: 99%
“…PVP is currently the most used polymer and is considered one of the best carriers [8,9,11,31,33,35,65,70,80,81,93,94,97,103,[115][116][117]123] since it is often allowed to obtain regular and spherical composite particles. PVP is followed by PLA [45,108,124] and PLLA [41,67,98,99,[111][112][113][118][119][120][121][125][126][127] that are also suitable carriers often employed. Recently, zein [17,46] is also established as a good polymeric carrier for SAS coprecipitation; moreover, β-CD [22,128] seems to be a promising polymer, but its use has to be further investigated given the very few existing papers.…”
Section: Sas Coprecipitation Of Active Compounds With Polymeric Carriersmentioning
confidence: 99%